Characterization of SCCmec, spa types and Multi Drug Resistant of methicillin-resistant Staphylococcus aureus isolates among inpatients and outpatients in a referral hospital in Shiraz, Iran - Zahra Hashemizadeh; Nahal Hadi; Samane Mohebi; Davood Kalantar-Neyestanaki; Abdollah Bazargani (BMC Research Notes, 2019)
Abstract Objectives Molecular typing such as spa typing is used to control and prevent Staphylococcus aureus widespread in hospitals and communities. Hence, the aim of this study was to find the most common types of S. aureus strain circulating in Shiraz via spa and SCCmec typing methods. Results Total of 159 S. aureus isolates were collected from two tertiary hospitals in Shiraz. Isolates were identified by biochemical tests. Antimicrobial susceptibility tests were performed by standard disk diffusion method and then genetic analysis of bacteria was performed using SCCmec and spa typing. In this study 31.4% of the isolates were methicillin-resistant S. aureus. The majority of isolates were SSCmec type III. Spa type t030 was the most prominent type among MRSA strains. For the first time in Iran, spa003, t386, t1877, t314, t186, t1816, t304, t325, t345 were reported in this study. It was shown that there is a possibility that these spa types are native to this region. Our findings showed that SCCmec II, III and IV disseminate from hospital to community and vice versa. Thus, effective monitoring of MRSA in hospital and community is necessary.